2012
DOI: 10.1371/journal.pone.0031985
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genetic Characterization of Pertactin-Deficient Bordetella pertussis in Japan

Abstract: The adhesin pertactin (Prn) is one of the major virulence factors of Bordetella pertussis, the etiological agent of whooping cough. However, a significant prevalence of Prn-deficient (Prn−) B. pertussis was observed in Japan. The Prn− isolate was first discovered in 1997, and 33 (27%) Prn− isolates were identified among 121 B. pertussis isolates collected from 1990 to 2009. Sequence analysis revealed that all the Prn− isolates harbor exclusively the vaccine-type prn1 allele and that loss of Prn expression is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
98
3
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 45 publications
11
98
3
5
Order By: Relevance
“…18,35 The rapid increase in pertactindeficient B pertussis in multiple countries, combined with evidence that several mutations can result in lack of pertactin, suggest pertactin deficiency may confer a selective advantage to the bacteria. 22,[38][39][40][41] More specifically, several recent studies indicate pertactin deficiency may especially benefit the bacteria among a highly immunized population. For instance, pertactindeficient strains were found to colonize mice primed with acellular pertussis vaccine more effectively than pertactin-expressing strains; a separate study found that acellular vaccinated individuals had twoto fourfold greater odds of being infected with a pertactin-deficient 5 rather than a pertactin-expressing B pertussis strain.…”
Section: Discussionmentioning
confidence: 99%
“…18,35 The rapid increase in pertactindeficient B pertussis in multiple countries, combined with evidence that several mutations can result in lack of pertactin, suggest pertactin deficiency may confer a selective advantage to the bacteria. 22,[38][39][40][41] More specifically, several recent studies indicate pertactin deficiency may especially benefit the bacteria among a highly immunized population. For instance, pertactindeficient strains were found to colonize mice primed with acellular pertussis vaccine more effectively than pertactin-expressing strains; a separate study found that acellular vaccinated individuals had twoto fourfold greater odds of being infected with a pertactin-deficient 5 rather than a pertactin-expressing B pertussis strain.…”
Section: Discussionmentioning
confidence: 99%
“…Although sequence diversity has also been observed in the vaccine immunogen pertactin (Prn), the circulating isolates recovered in the United States have become predominantly Prn deficient in recent years by one of at least 16 different mutations to the prn gene (16). The global emergence of Prn deficiency is well documented (16)(17)(18)(19), and deficiency may confer a fitness advantage during infection (20,21). While Prn deficiency appears to be more prevalent in isolates recovered from fully vaccinated patients, it does not appear to impact the effectiveness of acellular pertussis vaccines (22,23).…”
mentioning
confidence: 99%
“…In France, Bouchez et al noted that a significant percentage (5.6%) of the strains from studied hospitalized newborns below 6 months of age did not produce Prn [45]. Recently, Otsuka et al reported that Prn-deficient strains have significantly increased in B. pertussis populations since the early 2000s in Japan [47]. Both countries have molecular surveillance systems in place and report stable pertussis vaccination coverage for primary series [47,202,203].…”
Section: Teenagers/ Adolescentsmentioning
confidence: 99%
“…Recently, Otsuka et al reported that Prn-deficient strains have significantly increased in B. pertussis populations since the early 2000s in Japan [47]. Both countries have molecular surveillance systems in place and report stable pertussis vaccination coverage for primary series [47,202,203]. Antigenic mismatches between pertussis vaccine strains and circulating vaccine-evasive B. pertussis strains may alter the effectiveness of vaccine-induced immune responses through escape from immune recognition, as will be discussed below.…”
Section: Teenagers/ Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation